MECHANISM DESCRIBING INITIAL MICROALGAE ATTACHMENT ONTO POLYURETHANE FOAM PACKED IN FLUIDIZED BED BIOREACTOR FOR BULK BIOMASS HARVEST - MOHD SAHIB, AINUR ASSYAKIRIN (2018)
The potential to grow attached growth microalgae biomass species of Chlorella vulgaris in fluidized bed bioreactor was materialized in this research, targeting to ease the biomass harvesting process prior to biodiesel production.